SPE/IADC Drilling Conference 2007
DOI: 10.2118/105839-ms
|View full text |Cite
|
Sign up to set email alerts
|

Floatation of 10¾-in. Liner—A Method Used to Reach Beyond 10 km

Abstract: The requirement to drill longer wells to reach reserves on the boundaries of the Statoil operated Gullfaks Field required new solutions and techniques. The planning of the 10 km+ long well A-32 C presented a challenge where floatation technology was required. The 4660 m (15285 ft) long 10 3/4" liner was successfully floated to section TD at 7721 m (25324 ft) on May 9th 2006. The Gullfaks well A-32 C, named Gulltopp, is the longest well planned from an offshore installation with a planned TD at 10+ km. The simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…liner was run in hole with an 8 1 =4-in. reamer shoe to enable the liner to be worked down with rotation (Eck-Olsen et al 1994, 2007Alfsen et al 1995;Hjelle et al 2006). The actual torque values in the open hole showed that rotating the liner was impossible.…”
Section: Well Designmentioning
confidence: 99%
“…liner was run in hole with an 8 1 =4-in. reamer shoe to enable the liner to be worked down with rotation (Eck-Olsen et al 1994, 2007Alfsen et al 1995;Hjelle et al 2006). The actual torque values in the open hole showed that rotating the liner was impossible.…”
Section: Well Designmentioning
confidence: 99%
“…Mitchell (2002a, b) developed two new buckling solutions for horizontal wells by use of Jacobian elliptic functions. Recently, Gao and Miska (2008) studied the effects of end conditions and friction on static buckling in horizontal wells. They showed that if the dimensionless length of pipe is greater than 5p, the effects of boundary conditions can be ignored.…”
Section: Introductionmentioning
confidence: 99%